Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai Rumah Sakit Universitas Udayana - Masruchi, Humaidi; Noak, Piers Andreas; Supriliyani, Ni Wayan (CITIZEN CHARTER; Vol 1 No 2 (2019), 2019)
ABSTRACT   Udayana University Hospital is one of the state hospitals located in Bali, precisely in Jimbaran. Aside from being a forum for education and research, this hospital also has the main goal of providing quality and affordable health services for the entire community. Research with the title "The Influence of Leadership Style on Employee Performance" conducted at Udayana University Hospital employees aims to found out and explain the influence of leadership style on employee performance. And this study uses quantitative methods. The data collection tool used is a question by list to 117 employees. This data analysis used in this study is descriptive statistics and simple linear regression using the program on 22 of SPSS. The results of the study show partial influence of leadership style (X) on employee performance (Y) Udayana University Hospital is positive with the result is regression analysis linear with a value of 0.838.     Keywords: Leadership Style, Employee Performance, University Hospital Udayana